PENGARUH HASIL LATIHAN PEREGANGAN STATIS DAN DINAMIS TERHADAP KELENTUKAN TOGOK MENURUT JENIS SEX ANAK KELAS 3 DAN 4 SEKOLAH DASAR - Suharjana, Fredericus (Jorpres (Jurnal Olahraga Prestasi), 2010)
This research aims to know: 1) the different of the influence between static and dynamic stretching toward the togok flexibility for children in the III and IV grade of elementary school; 2) the different of togok flexibility between male and female students of III and IV grade of elementary school; 3) the interaction between the stretching exercise result and gender type toward togok flexibility of III and IV grade students of elementary school.The research method used was experimental. The research population was all male and female students in III and IV grade of elementary school in Kulon Progo regency which was 261 elementary schools with 6.469 students. The research sample was determined by multi stage random sampling that was UPTD PAUD DIKNAS Ngemplak elementary school in Kalibawang with 20 male students and 20 female students. The research instrument used to know the level of togok flexibility was the series of tests that had compiled by the writer and has been tested. Reliability coefficient was got by Hoyt technique, the result of total reliability coefficient for male students was 0.719 and for female students was 0. 700. Validity coefficient was got by total part technique, the result of togok flexibility test for male students was forward r= 0.657, backwarc..l r=0.627, lo lfle riyhl ::,ic..le r=0.852 and to the left side r= 0.711. Moreover, togok flexibility for female students was: forward r= 0.600, backward r= 0.645, to the right side r= 0.827, and to the left side r= 0.829. All significance was on the level a + 0.05. Data analysis technique used was ANA VA 2 x 2 on the significance level a= 0.05.The result ofF-test was 1) static and dynamic stretching as variable A was got Fa = 45.565 > Ft = 4.11, it means that F0 was rejected and Ha was accepted, means that there was a the different of the influence between static and dynamic stretching toward the togok flexibility for children in the III and IV grade of elementary school, 2) male and female gender as variable 8 was got F0 = 1.865 < Ft = 4.11 means that Ho was accepted and Ha was rejected, means that there was no the different of togok flexibility between male and female students of III and IV grade of elementary school; 3) for inter AB that was the interaction between the stretching exercise result and gender type toward togok flexibility of III and IV grade students of elementary school was got Fa = 3.292 < Ft = 4.11 means that Ho was accepted and Ha was rejected means that there was no interaction between the stretching exercise result and gender type toward togok flexibility of III and IV grade students of elementary school. Keywords: stretching exercise, flexibility, static, dynamic, togok